2022
DOI: 10.1038/s41598-021-04600-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adult neurogenesis by the endocannabinoid-producing enzyme diacylglycerol lipase alpha (DAGLa)

Abstract: The endocannabinoid system modulates adult hippocampal neurogenesis by promoting the proliferation and survival of neural stem and progenitor cells (NSPCs). This is demonstrated by the disruption of adult neurogenesis under two experimental conditions: (1) NSPC-specific deletion of cannabinoid receptors and (2) constitutive deletion of the enzyme diacylglycerol lipase alpha (DAGLa) which produces the endocannabinoid 2-arachidonoylglycerol (2-AG). However, the specific cell types producing 2-AG relevant to neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Another potential pathway with which astrocytes promote neurogenesis and survival is possibly through the endocannabinoid system [25]. It has been demonstrated that the endocannabinoid 2-arachidonoylglycerol (2-AG) is neuroprotective through the receptor CB1R [26].…”
Section: Astrocytes Secrete Various Molecules That Are Beneficial To ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential pathway with which astrocytes promote neurogenesis and survival is possibly through the endocannabinoid system [25]. It has been demonstrated that the endocannabinoid 2-arachidonoylglycerol (2-AG) is neuroprotective through the receptor CB1R [26].…”
Section: Astrocytes Secrete Various Molecules That Are Beneficial To ...mentioning
confidence: 99%
“…It has been demonstrated that the endocannabinoid 2-arachidonoylglycerol (2-AG) is neuroprotective through the receptor CB1R [26]. Astrocytes might be an important player in this as the deletion of diacylglycerol lipase alpha (DAGLA) in astrocytes, a gene producing a necessary enzyme for 2-AG pro-duction, negatively affected neuron survival and neurogenesis, suggesting that astrocytes play an important role in neurogenesis through the endocannabinoid pathway [25].…”
Section: Astrocytes Secrete Various Molecules That Are Beneficial To ...mentioning
confidence: 99%
“…For example, postsynaptic DAGLα activity is required for the growth of inhibitory boutons at dendrites receiving strong excitation in the CA1 region (Hu et al, 2019). Astrocytic DAGLα expression is involved in the regulation of adult hippocampal neurogenesis, through the synthesis of astroglial 2-AG and activation of neuronal CB1 receptor (Schuele et al, 2022).…”
Section: Regulation Of 2-ag Synthesismentioning
confidence: 99%
“…For example, in NSCs from early postnatal rats, DG cell proliferation requires CB1 receptor and CB2 receptor co-activation while SVZ cell proliferation is increased with CB1 receptor activation and lost with co-activation (Rodrigues et al, 2017). Genetic deletion of DAGLα from NSC and NPCs in the hippocampal DG results in strongly impaired neurogenesis, producing a 50% decrease in proliferation of cells (Schuele et al, 2022), suggesting that 2-AG-mediated signaling is required for proper neurogenesis. On the other hand, ABHD4, a serine hydrolase that can contribute to non-NAPE-PLD-mediated AEA synthesis (Simon & Cravatt, 2006), is necessary and sufficient for anoikis of radial glia progenitor cells that have inappropriately detached from the ventricular wall in response to alcohol exposure (Laszlo et al, 2020).…”
Section: Ecs System and Neurotrophismmentioning
confidence: 99%
“…Since mouse aging is associated with similar alterations, investigating CIC expression pattern and functional role in the SGZ of aging mice is a promising direction. Another hint to the molecular mechanisms potentially leading to neurogenic aging comes from the study of Schuele et al, which shows that diacylglycerol lipase alpha (Dagla), the main cannabinoid (CB)-producing enzyme, is expressed in SGZ NSPCs and, at higher levels, in granular neurons 11 . Dagla deletion in NSPCs and astrocytes, but not in neurons, impaires SGZ neurogenesis, suggesting that autocrine CB signaling in NSPCs may be required for their proliferation and/or lineage progression.…”
mentioning
confidence: 99%